The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1017/s1092852900020137
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia Nervosa in Identical Triplets

Abstract: The cause of anorexia nervosa (AN) is unclear, but is likely multifactorial, including psychological, familial, environmental, societal, genetic, and other biological factors. This case report of identical 12-year-old female triplets simultaneously concordant for AN illustrates the importance of addressing all these components in evaluation and treatment, and the difficulty of determining the relative importance of each factor in the cause of an individual's eating disorder. An overly close relationship and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Occurring predominantly during adolescence (Halmi et al 1979) the disease is characterised by a pathological obsession for thinness through the control of eating behaviour. Evidence from family and twin studies have suggested that both genetic and environmental components contribute to the development of AN (Vandereycken and Pierloot 1981;Garfi nkel and Garner 1982;Lilenfeld et al 1998;Fairburn et al 1999;Sokol et al 2009). The genetic component has been estimated through meta analysis of twin studies as contributing up to 76% of the susceptibility to AN (Treasure and Holland 1990;Klump and Culbert 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Occurring predominantly during adolescence (Halmi et al 1979) the disease is characterised by a pathological obsession for thinness through the control of eating behaviour. Evidence from family and twin studies have suggested that both genetic and environmental components contribute to the development of AN (Vandereycken and Pierloot 1981;Garfi nkel and Garner 1982;Lilenfeld et al 1998;Fairburn et al 1999;Sokol et al 2009). The genetic component has been estimated through meta analysis of twin studies as contributing up to 76% of the susceptibility to AN (Treasure and Holland 1990;Klump and Culbert 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, three studies involved qualitative interviews with individuals with EDs and found participants perceive competition with their siblings as a possible factor in the development and maintenance of their ED (Bachner‐Melman, 2005; De Bruin & Oudejans, 2018; Rowland, 2009). Similarly, four case studies highlighted general competitive attitudes towards siblings in people with EDs, including a set of triplets who competed with each other to be the thinnest (Halperin, 1996; Lazerson, 1984; Smith, 2011; Sokol et al., 2009).…”
Section: Resultsmentioning
confidence: 99%